STANDARISASI INSTRUMEN INTEGRATED ASSESSMENT HASIL BELAJAR BAHASA DENGAN PROGRAM QUEST - Suyata, Pujiati; Hidayanto, Nur; Widyantoro, Agus (LITERA, 2014)
This study aims to produce a model of standardized convergent and divergent integrated-assessment instruments for Indonesian and English learning outcomes at junior high schools using Item Response Theory. It employed a research and development design. In the first year, a learning continuum was developed, followed by the development of integrated assessment instruments based on the learning continuum. Instrument standardization was then conducted using 1-PL Item Response Theory and the QUEST program. The results of the first year were 30 standardized integrated assessment instrument sets, a guidebook for construction of the integrated assessment instruments for language learning outcomes and the QUEST program guidebook. In the second year, the integrated assessment instruments for language learning outcomes were disseminated in provinces of Yogyakarta Special Territory, South Kalimantan, and West Nusa Tenggara.